Bleeding Mud: The Testimonial Poetry of Hurricane Mitch in Nicaragua - Erin S Finzer (Studies in 20th & 21st Century Literature, 2015)
Beginning with Rubén Darío, Nicaragua has long prided itself in being a country of poets. During the Sandinista Revolution, popular poetry workshops dispatched by Minister of Culture Ernesto Cardenal taught peasants and soldiers to write poetry about everyday life and to use poetry as a way to work through trauma from the civil war. When Hurricane Mitch–one of the first superstorms that heralded climate change–brought extreme flooding to Nicaragua in 1998, poetry again served as a way for victims to process the devastation. Examining testimonial poetry from Hurricane Mitch, this article shows how the mud and despair of this environmental disaster function as palimpsests of conquest and imperial oppression.
Keywords: Hurricane Mitch; Nicaragua; testimonial poetry; climate change; testimony; environmental injustice